Clinical Observation of a Child with Congenital Adrenogenital Syndrome - T.V. Sirenko; A.A. Khotsenko; O.N. Plakhotnaya (Zaslavsky O.Yu., 2012)
This article describes the features of congenital adrenogenital syndrome course in a newborn. We hope the description of this clinical case will add to the knowledge about this rare congenital disease.